THE ROLE OF THE COMMUNITY GUARDIAN (WALIPAS) IN INCREASING THE RELIGIOUS MOTIVATION OF CHILDREN IN CARE WHO ARE CASES OF SEXUAL VIOLENCE AT THE CLASS I BLITAR SPECIAL CHILDREN'S GUIDANCE INSTITUTION (LKPA) - Prasetya Adhi Nugraha; Herry Fernandes Butar Butar (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the role of Correctional Counselors (Walipas) in enhancing the religious motivation of juvenile inmates involved in sexual violence cases at the Class I Blitar Special Child Development Institution (LPKA). The research is motivated by the complex challenges faced by these juveniles, including psychological trauma, identity crises, and low motivation to practice religious values, while spiritual development has not yet been fully prioritized in the correctional setting. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving correctional counselors, juvenile inmates, and religious instructors. The analysis is based on the five dimensions of religious motivation proposed by Nico Syukur Dister. The findings reveal that Walipas play a multifaceted role, not only as administrative supervisors but also as spiritual mentors, psychological companions, and agents of social recovery. Through personal guidance and educational approaches, they help inmates better understand religious values, rebuild self-confidence, and develop a commitment to positive behavioral change. Religious development programs include Qur’anic learning, worship guidance, and individualized spiritual counseling. Despite these positive outcomes, several challenges remain, such as limited human resources, heavy workloads, and inadequate facilities. Nevertheless, observable improvements in behavior and religiosity among some inmates indicate that this approach is effective. The study concludes that Walipas have a strategic role in fostering religious motivation, which can serve as a foundation for personal transformation and reducing the likelihood of reoffending. Strengthening counselor capacity, increasing the number of facilitators, and developing more structured and sustainable programs are recommended to enhance the effectiveness of spiritual rehabilitation. Keywords: Correctional Counselor; Religious Motivation; Juvenile Inmates; LPKA